THE DOCTRINE OF ADVERSE POSSESSION IN MODERN PROPERTY LAW: A REASSESSMENT - Adedokun, Isa Akanji (LexScriptio A Journal of the Department of Jurisprudence and Public Law, 2025)
Adverse possession is a legal doctrine that permits a trespasser to acquire title to land by continually occupying it for a prolonged period, usually twelve years, without the authorisation of the land owner. This doctrine occurs when a stranger takes over land he does not own. This situation of possession can happen intentionally or unintentionally, with a squatter or trespasser occupying the land, such as when someone unknowingly encroaches on the land of his neighbour. This doctrine has become rooted in the property law of many jurisdictions. Still, modern intricacies are challenging this age-long rule in a bid to balance the competing interests of adverse possessors and true owners. Against this background, this paper examines the theoretical underpinnings of adverse possession, the evolution of the doctrine through case law and statutory limitations, and the modern challenges and criticism of adverse possession. It renders policy reforms as recommendations for the modification of the doctrine or total expulsion from the realm of modern property law. The paper accentuates the contemporary realities of absentee landlords or land owners and as part of its findings, contends that the social policy considerations of adverse possession are contrary to fairness and justice and tantamount to enabling land grabbing. The article recommends the remedy of compensation for the landowner or abolition of title to land through adverse possession as done in Singapore.